LOWERING THE RISK FOR THROMBUS AND STROKE IN ATRIAL FIBRILLATION PATIENTS: Will Dabigatran Replace Warfarin? - Tan, Alex Y. (2013)
The use of oral anticoagulation to reduce stroke risk from thromboembolism has become the cornerstone of management of atrial fibrillation. Dabigatran is a direct thrombin inhibitor, which in contrast to warfarin, does not require regular blood draws for monitoring effect. Randomized controlled studies suggest that dabigatran may be more effective than warfarin at higher doses without an increased bleeding risk, and equally effective at lower doses, with lower bleeding risk. With these apparent advantages comes a higher cost, and limited use in patients with underlying renal or liver disease. In addition, the inability to measure anticoagulant effect, as with warfarin, presents a double-edged sword for clinical use of dabigatran. In this review, we discuss the mechanisms of action, clinical effect, and place in therapy of dabigatran as a possible replacement for warfarin.